PENGARUH PEMANFAATAN FASILITAS BELAJAR DAN KEAKTIFAN BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI SISWA KELAS XI SMA NEGERI 1 PLAOSAN TAHUN PELAJARAN 2013/2014 - Jahnudin Abdullah Nurrachsid (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2014)
This study measured the effect of the use of facilities on student learning and activity of learning on student achievement . In collecting the data using a questionnaire and the results are then expressed in terms of numbers. This research was conducted at SMAN 1 Plaosan, Magetan Academic Year 2013/2014. The subjects were students of class XI SMA Negeri 1 Plaosan, Magetan. Collecting data in this study using a questionnaire. Questionnaires were prepared and tested first tested for validity and reliability to determine the level of piety and reliability of the questionnaire . Data analysis techniques using multiple linear regression analysis, the F test, T test sample into a number of research subjects XIA class is 21 students. In sampling saturated researchers using sampling techniques. Saturation sampling technique is usually done because of some particular considerations of the researcher Mass because of limited time, energy and money as well as the distance between the place of domicile of researchers,with,research. The results showed: The influence Utilization Facilities Student Learning and Motivation Against Student Achievement In Class XI Subject Accounting at SMA Negeri 1 Plaosan Magetan Semester Academic Year 2013/2014 . This is evidenced by the results of calculations obtained value F calculated = 20.362 while F table = 3.55 at significance level of 0.05 shows that the calculated F = 20.362 > F table = 3.55 , so it can be concluded that there are significant use of learning facilities and activeness learning on student achievement.